Regulation of Phosphorylation of a Specific Protein in Toad-Bladder Membrane by Antidiuretic Hormone and Cyclic AMP, and Its Possible Relationship to Membrane Permeability Changes - DeLorenzo, Robert J. (1973)
Phosphorylation of a specific protein was decreased in intact toad bladders by exposure to either antidiuretic hormone or monobutyryl cyclic AMP. The decrease in phosphorylation caused by these agents preceded the change in electrical potential difference (an indicator of the rate of sodium ion transport) observed in response to the same compounds. The addition of cyclic AMP to homogenates of toad bladder led to a decrease in phosphorylation of the same, or a similar, protein. In subcellular fractionation studies, the effect of cyclic AMP on the phosphorylation of this protein was observed in those fractions rich in membrane fragments, but not in the nuclear or cell-sap fractions. These and other results are compatible with the possibility that the regulation by vasopressin and cyclic AMP of sodium and/or water transport in toad bladder may be mediated through regulation of the phosphorylation of this specific protein.